Internalisasi Nilai-Nilai Pendidikan Islam dalam Mencegah Perilaku Bullying Pada Peserta didik di SD Islam Al-Mu’min - Seftiani, Adinta Salsabila; Nur Fuad, Ai Fatimah (CV. Creative Tugu Pena, 2024)
The education world is currently experiencing a surge in bullying cases. Various efforts are being made within school environments through the internalization of educational values, particularly Islamic education, which serves as the main foundation in shaping children's characters to prevent bullying behavior. This research aims to explore in depth how the internalization of Islamic educational values can help prevent bullying behavior within school environments. Thus, this study can provide profound insights into school efforts in internalizing Islamic values that are expected to shape students' characters and prevent negative behaviors such as bullying. This research adopts a qualitative approach using three types of data: documentation study, observation, and interviews, employing a descriptive method. The findings of the research conducted at SD Islam Al-Mu'min demonstrate that the process of internalizing Islamic educational values involves instilling Islamic values such as faith, morality, worship, and social interaction. The internalization of Islamic educational values is manifested through school activities such as the 5S program (smile, greet, chat, be polite, be kind), Quran memorization, congregational prayers, and Friday prayers, through exemplary behavior, habituation, and advice. By internalizing these Islamic educational values, students' characters are shaped, thus preventing bullying behavior in schools. Keywords: Internalization, Islamic Educational Values, Bullying Behavior